Interim Performance Feedback in Multistage Tournaments: The Optimality of Partial Disclosure - Goltsman, Maria; Mukherjee, Arijit (Journal of Labor Economics, 2011)
Workers competing in a tournament for a prize (e.g., a promotion) often perform sequentially in multiple stages. When the firm is privately informed about the workers’ performance, it can sharpen incentives by strategically disclosing the intermediate results. But the policies that enhance final-stage effort may dampen incentives at the intermediate stage. In our model, the optimal disclosure policy has a simple form: disclose only if all workers perform poorly. This result offers a novel justification for partial disclosure in performance feedback. Also, it contrasts with the existing literature that focuses on the extreme policies of full disclosure and no disclosure.